PKM Pelatihan Aplikasi Program 3D Gambar Bangunan Pada Guru-Guru dan Siswa SMK (Program Revit dan Sketch Up) - M. Reza Hasrul; Ahnaf Riyandirga A; Ahmad Wahidiyat; Moeh. Kay Muddin Asnur; Iriandy Iriandy (PT. Global Research Collaboration, 2024)
Vocational education plays a crucial role in preparing a skilled workforce ready to meet the dynamic needs of the industry. Vocational High Schools (SMK) in Indonesia are expected to equip students with skills that align with current industry requirements, particularly in construction technology and architecture. Mastery of 3D design applications such as Revit and SketchUp is highly essential. However, previous studies have indicated that proficiency in these applications remains limited among SMK teachers and students, primarily due to inadequate training and lack of sufficient resources. This study employs action research methods to enhance the competencies of SMK teachers and students in using Revit and SketchUp. The methodology includes cycles of planning, implementation, and observation. Training outcomes reveal significant improvements among teachers, while students still require additional field knowledge to use the software effectively. To optimize training results, it is necessary to include additional modules on field knowledge, real-world projects, and projectbased learning (PBL). PBL has proven to enhance both technical skills and soft skills such as communication and time management. Furthermore, industry involvement in projects offers valuable practical insights. Integrating project-based learning and industry partnerships is a crucial strategy in vocational education to ensure that SMK graduates are well-prepared to meet the evolving demands of the industry